Microbiological Quality of Milk Flavored Ready to Drink and Hygiene Practice of Street Vendors - Herwin Pisestyani; Irena Ivania; Ardilasunu Wicaksono; Denny Widaya Lukman; Mirnawati Sudarwanto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
Milk products consumption has become a new trend of healthy lifestyle among students in order to meet appropriate daily nutrients. This study was aimed to measure the total number of microbes found in milk drinks sold around the IPB Dramaga and Cilibende and to determine factors that influence it. Samples were collected from 13 milk vendors within radius of 2 kilometers from outermost point of campus and taken with 3 repetitions. Calculation of the total number of microbes was done by using the plate count method in accordance with SNI 2897-2008 about testing method of microbial contamination in meat, eggs, and milk, as well as processed products and SNI 01-6366-2000 about the maximum limit of microbial contamination in food. Risk factors’ data was taken by interviewing milk drinks seller using structured questionnaire. Factors that influenced microbial contamination were analyzed using Chi-Square test. The results showed that 74.4% of milk drinks samples had a high total number of microbes. The average total number of microbes in Dramaga and Cilibende samples was 1.0 x 105 ± 1.4 x 105 cfu / ml and 1.1 x 107 ± 1.2 x 107 cfu/ml. The total number of microbes are significantly influenced (p<0.05) by equipments used, the cleanliness of the equipment, the cleanliness of the table, washing hands practice, and the distance from the crowd. The high number of microbial contamination in milk drinks could damage the quality of milk and shorten the shelf life.